MEDICAL PROFESSIONAL’S EMIGRATION: CAUSES AND THE CONSEQUENCES - Janusauskas, Antanas; Tumas, Valentinas (European Scientific Journal, ESJ, 2014)
The consequences of emigration of health professionals in Lithuania are perceived rather negatively. Emigration of Lithuanian health professionals is seen as a loss of investments made in the process of preparing healthcare personnel. Medical or healthcare related studies are expensive and they are offered to Lithuanian citizens for free, whereas the skills and knowledge passed to students may be used in other countries, where work opportunities are much better than in Lithuania. However, the economic reason still prevails. Health professionals want to work and get such remuneration for their work that will allow them to live on a quite good level. Salary of our physicians is not low, but keeping in mind, that physician’s work is very hard, responsible, requiring permanent training and skills development, the salary should be yet higher. In other countries the medical professions are respected, have higher position in the hierarchy of respected professions. Emigration of health professionals has been an object of much policy discussion in the global context for many years, however, in Lithuania it is a new phenomenon.